Disclosure of Contingent Environmental Liabilities: Some Unintended Consequences? - Kennedy, Jane; Mitchell, Terence; Sefcik, Stephan E. (Journal of Accounting Research, 1998)
Disclosures, Contingent liabilities, SFAS No. 52, Environmental liability